Computer-aided design of 3D woven composites with complex topologies - Liu, Binghui (Kansas State University, 2021)
Three-dimensional woven fabrics with various structures have wide applications in many technical fields. These applications include aerospace, automotive, construction, medical, energy, military, and more. Due to the complex structures, the design process of 3D woven fabrics is time-consuming and error-prone. This report introduces a new algorithm of CAD/CAM tool to design 3D woven textile structures. This developed algorithm represents warp yarns paths and weft yarns paths using symmetric matrices. Hence it allows technical weavers to design woven fabrics in both weft plane and warp plane. Users provide input data by graphing the yarn paths precisely. The CAD/CAM design tool uses this data to generate weft matrices and warp matrices, then calculate a 2D binary weaving matrix automatically. This weaving matrix can be used to produce 3D woven fabric on a conventional jacquard weaving loom. This paper provides the design processes of various three-dimensional woven fabrics by using this CAD/CAM tool, such as T, Pi, I-beam, truss, tubular structure, and some other near-net-shape structures. Furthermore, this article discusses the assembly part of this algorithm. Weavers can assemble fabrics in both warps and wefts directions to generate more complex structures.
Keywords: CAD/CAM; 3D woven fabric